Microstructural characterization of integrally directionally solidified Nb-Si based alloys at high withdrawal rates. (July 2019) - Fang, Xin; Guo, Xiping; Qiao, Yanqiang
Abstract: The Nb-Si based alloys were integrally directionally solidified at 2050 °C with withdrawal rates ranging from 100 to 1000 μm/s to reveal the microstructural evolution at high withdrawal rates. At the withdrawal rates of 100, 200 and 300 μm/s, the morphology of the solid/liquid (S/L) interface is cellular structure, and the NbSS /γ-(Nb, X)5 Si3 eutectic exhibit radial lamellar structure and the primary γ-(Nb, X)5 Si3 phases presents hexagonal structure. When the withdrawal rate exceeds 500 μm/s, the S/L interface transforms into divergent dendrite structure, and rod-like eutectics and H-type primary γ-(Nb, X)5 Si3 phases occur. The morphological evolution of eutectic is mainly accompanied with the decrease in volume fraction of γ-(Nb, X)5 Si3 phases in eutectic. Besides, both the average size and the interphase spacing of the eutectic cell/dendrite decrease gradually with increasing withdrawal rate. Moreover, the segregation degree for Ti and Cr increases initially and then decreases with increase in withdrawal rate, which is corresponding with the variation in volume fraction of segregation phases at cellular/dendrite boundary. Graphical abstract: Image 1 Highlights: Morphology of S/L interface transforms from cellular to dendrite structure when withdrawal rate exceeds 500 μm/s. Decreasing in volume fraction of γ-(Nb, X)5 Si3 phases drives the eutectic evolution from lamellar to rod structure. Segregation degree of Ti and Cr increases initially and then decreases with increasing withdrawal rate.